6-Methoxy-5, 6-dihydrochelerythrine suppresses PANC-1 cells by down-regulating the Ras/Raf/Mek/Erk pathway. (October 2018) - Wu, Si-zhi; Wu, Xian-lin; Zhou, Guang-xiong; Deng, Li; Pang, Peng; Tang, Hui; Xu, Hua-chong; Shi, Yu-cong; Chen, Xiao-yin
Graphical abstract: Highlights: 6-methoxy-5, 6-dihydrochelerythrine is a alkaloid extracted from Radix zanthoxyli . MDC can inhibit cell proliferation and induce apoptosis of PANC-1 cells. MDC can inhibit migration and invasion of PANC-1 cells. MDC can down-regulate the Ras/Raf/Mek/Erk pathway of PANC-1 cells. Abstract: To investigate the suppression of PANC-1 pancreatic cancer cells by 6-methoxy-5, 6-dihydrochelerythrine (MDC), which is a novel natural product from Radix zanthoxyli, and its underlying mechanism. PANC-1 cells were treated with MDC. Cell proliferation, cell cycle, apoptosis and cell migration or invasion abilities were measured by MTT, flow cytometry assays and invasion assays, respectively. The expression of Ras protein and the inhibition of the downstream Raf/Mek/Erk signalling pathway were measured by western blot. The results showed that MDC can inhibit the cell viability and induce the apoptosis of PANC-1 cells. MDC could inhibit the cell migration or invasion of PANC-1 cells, down-regulate the expression of the Ras protein and inhibit the downstream Raf/Mek/Erk pathway in PANC-1 cells. MDC can inhibit the cell proliferation, apoptosis, migration and invasion abilities of PANC-1, which may be related to the regulation of Ras and its downstream Raf/Mek/Erk signalling pathway.